Discordance Between Online Information and Male Hypogonadism Clinical Guidelines: A Global Multilingual Content Analysis. - Grant,B; de,Silva NL; Gumssani,M; Quinton,O; Kayali,F; Gamage,IL; Dhillo,WS; Grossmann,M; Jayasena,CN (J Clin Endocrinol Metab, 2026)
CONTEXT: Testosterone prescriptions have increased up to 12-fold globally over the past 2 decades. EU and UK law tightly regulate the advertising of medical products. OBJECTIVE: To review the accuracy of publicly accessible information on websites offering testosterone treatment. DESIGN/SETTING: Content analysis methodology using concept- and data-driven strategies to develop a coding frame for data extraction. Publicly accessible websites offering testosterone prescriptions were identified using predefined search terms, conducted in English, Arabic, Hindi, and Spanish, across 3 search engines. Virtual private network searches within multiple geographical regions were used to reduce location bias. MAIN OUTCOME MEASURE: Accuracy of extracted data determined using international guidelines. RESULTS: A total of 253/1138 websites were included (144 US/Canada; 48 Europe; 17 Australia; 12 Asia; 11 South America; 10 Middle East). The following non-guideline-based practices (with numbers/percentages of clinics) were identified: routinely use nontestosterone androgens or testosterone secretagogues (eg, gonadotrophins) to treat symptomatic low testosterone (61/253; 24.4%); testosterone treatment reduces cardiovascular risk (52/253; 20.6%); microdosing improves treatment effects (30/253; 11.9%); testosterone is prescribed for men with normal serum testosterone (>12nmol/L; 25/253;9.9%); testosterone has antiaging effects (25/253; 9.9%). US-based clinics more frequently made non-guideline-based claims compared with other geographical locations. CONCLUSION: We identify serious and frequent breaches of advertising law and regulations by clinics around the world offering testosterone treatment, with the potential to cause harm to men. We recommend enforcement of existing laws by national regulators to address this widespread public health challenge and align patient expectations with clinical guidelines for the safe treatment of men.